Pharmacological treatment of central neuropathic pain: consensus of the Brazilian Academy of Neurology - Oliveira, Rogério Adas Ayres de; Baptista, Abrahão Fontes; Sá, Katia Nunes; Barbosa, Luciana Mendonça; Nascimento, Osvaldo José Moreira do; Listik, Clarice; Moisset, Xavier; Teixeira, Manoel Jacobsen; Clinicians participants of the panel of experts recommended by the Brazilian Academy of Neurology; Andrade, Daniel Ciampi de (Arquivos de Neuro-Psiquiatria, 2020)
Background: Central neuropathic pain (CNP) is often refractory to available therapeutic strategies and there are few evidence-based treatment options. Many patients with neuropathic pain are not diagnosed or treated properly. Thus, consensus-based recommendations, adapted to the available drugs in the country, are necessary to guide clinical decisions. Objective: To develop recommendations for the treatment of CNP in Brazil. Methods: Systematic review, meta-analysis, and specialists opinions considering efficacy, adverse events profile, cost, and drug availability in public health. Results: Forty-four studies on CNP treatment were found, 20 were included in the qualitative analysis, and 15 in the quantitative analysis. Medications were classified as first-, second-, and third-line treatment based on systematic review, meta-analysis, and expert opinion. As first-line treatment, gabapentin, duloxetine, and tricyclic antidepressants were included. As second-line, venlafaxine, pregabalin for CND secondary to spinal cord injury, lamotrigine for CNP after stroke, and, in association with first-line drugs, weak opioids, in particular tramadol. For refractory patients, strong opioids (methadone and oxycodone), cannabidiol/delta-9-tetrahydrocannabinol, were classified as third-line of treatment, in combination with first or second-line drugs and, for central nervous system (CNS) in multiple sclerosis, dronabinol. Conclusions: Studies that address the treatment of CNS are scarce and heterogeneous, and a significant part of the recommendations is based on experts opinions. The CNP approach must be individualized, taking into account the availability of medication, the profile of adverse effects, including addiction risk, and patients' comorbidities.
Keywords: Pain; Pain management; Neuropathic pain; Drug therapy; Consensus